Konsep Pendidikan Akhlak Perspektif Hadratus-Syaikh KH. Muhammad Hasyim Asy’ari - Mukhlishah, Ulfatul; Faiz, Muhammad Nur; Jumari, Jumari (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
The goal of moral education in Islam is to develop positive traits in humans so that their morality will develop, so that they are always open to doing good and able to distance themselves from all forms of evil. Thus, a person can become a human being who has good morals and is responsible. Meanwhile, according to the concept of Hadratus-Shaykh KH. Hasyim Asy'ari in the book Adabul Alim Wal Muta'alim has provided an educational treatise that talks a lot about the moral education of teachers and students so that in the book we can understand and know in depth about the content of moral education properly. And he also colored education in Indonesia and among Islamic boarding schools. This research is a library research (Library Research) which is included in qualitative research. Data was collected through primary and secondary data sources after which the data was analyzed using a descriptive approach. This study states that in the book Adabul Alim wal Muta'alim, moral education is thoroughly integrated into the learning process. KH. Hasyim Asy'ari emphasized the importance of being calm and gentle for a teacher in interacting with his students. Likewise, students are expected to have morals that sincerely respect their teachers. In the context of learning, morality for students means always prioritizing learning by starting from the most important things to the depth of the discussion. The moral relationship between teacher and student actually reflects mutual respect and trust, which is built on awareness and respect between the two during the learning process. Ethics in interacting between teachers and students is considered as a real form of obedience to Allah and His Messenger. All of this shows that the harmonious relationship between the two parties cannot be separated from the spiritual values that are upheld in Islamic teachings